Labor Market Power and Development - Tristany Armangué-Jubert; Nezih Guner; Alessandro Ruggieri (Institute of Labor Economics (IZA), 2023)
Imperfect competition in labor markets can lead to efficiency losses and lower aggregate output. In this paper, we study whether differences in competitiveness of labor markets can help explain differences in GDP per capita across countries. We structurally estimate a model of oligopsony with free entry for countries at different stages of development and show that the labor supply elasticity, which determines the extent of firms' labor market power, is increasing with GDP per capita. Wage mark-downs range from 55 percent among low-income countries to around 23 percent among the richest. Output per capita in poorer countries would increase by up to 69 percent if their labor markets were as competitive as in countries at the top of the development ladder.
Keywords: J42; L13; O11; E24; 330; labor market power; oligopsony; development; inequality